A high-elasticity and high-toughness low-frequency radar absorbing material and preparation method thereof

By using two-component polyurethane resin and a sheet-like microwave absorber after surface coating in low-frequency radar absorber, and adding a variety of additives, the problem that existing materials are difficult to have high toughness and high elasticity at the same time is solved, and efficient low-frequency electromagnetic wave absorption and excellent construction performance are achieved.

CN116496690BActive Publication Date: 2025-03-11AVIC BEIJING INST OF AERONAUTICAL MATERIALS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211244186.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-12
Publication Date
2025-03-11
Estimated Expiration
2042-10-12

AI Technical Summary

Technical Problem

While meeting the requirements of electromagnetic wave absorption performance, existing low-frequency radar absorbing materials are difficult to have high toughness and high elasticity at the same time. In addition, sheet-like absorbing agents are prone to irregular stacking, forming pores, and destroying the overall performance of the absorbing coating.

Method used

A two-component polyurethane resin is used as a matrix, and a sheet-like microwave absorber after surface coating is carried out by an amino alcohol mixture with a long-chain molecular structure as a filler, and an organic dispersant, a defoaming agent, a softening agent, and a diluent are added to improve the interface characteristics between the absorber and the resin.

Benefits of technology

It is achieved to improve the overall toughness and elasticity of the wave absorbing coating while ensuring the absorption performance of low-frequency electromagnetic waves, meet the comprehensive requirements of excellent construction performance, and produce low-frequency radar wave absorbing materials that have both high elasticity and high toughness.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a high-elasticity and high-toughness low-frequency radar absorbing material and a preparation method thereof, belonging to the technical field of radar stealth materials. The present invention is compounded by two-component polyurethane, a sheet-shaped microwave absorbent filler treated with amino alcohol surface, an organic dispersant, a defoamer, a softener and a diluent. The two-component polyurethane accounts for 19% to 45% of the mass of the absorbing coating, and the microwave absorbent filler is a sheet-shaped composite ferromagnetic material containing iron, cobalt and nickel, which is prepared after the surface is coated with amino alcohol, accounting for 54% to 80% of the mass of the coating. The mass fraction of the organic dispersant, the defoamer and the softener in the coating is 0.1% to 10%. The remainder is a diluent. The preparation steps of the present invention are: dissolving and diluting the two-component polyurethane with a diluent, and then adding a microwave absorbent filler, an organic dispersant, a defoamer and a softener to compound. The preparation method of the present invention can improve the toughness and elasticity of the low-frequency radar absorbing coating, and at the same time has excellent construction performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electromagnetic wave absorbing materials and radar stealth materials, and designs a high-elasticity and high-toughness low-frequency radar absorbing material and a preparation method thereof. Background Art

[0002] Stealth technology is a key technology in the modern military field. It is crucial to improve the survivability of various military equipment and weapons in modern battlefields, reduce the detection rate, and further break through the enemy's electromagnetic defense. Radar absorbing materials can effectively absorb radar waves, significantly weaken the reflected waves and make them difficult to be detected by radar receivers. They are an important material basis for realizing the stealth technology of weapons and equipment. In recent years, low-frequency radar detection technology has been studied in various countries due to its advantage of longer detection distance. Correspondingly, low-frequency radar absorbing materials can effectively reduce the detection rate of targets when detecting low-frequency radar waves. Low-frequency radar absorbing materials generally use ferromagnetic materials with sheet-like structural characteristics and higher magnetic permeability as absorbers, and organic polymer resins with good toughness and elasticity as the matrix. Compared with spherical absorbers, sheet-like absorbers have a larger specific surface area, and the performance of the interface between the absorber and the resin has a greater impact on the overall physical and chemical properties of the absorbing material. In addition, sheet-like absorbing materials are anisotropic and prone to irregular stacking to form pores, which will further destroy the toughness and elasticity of the absorbing coating. In order to meet the high strength, high toughness, high elasticity and other requirements of low-frequency radar absorbing materials for aircraft, ships, missiles and other weapons and equipment, surface coating of flaky absorbers to improve the interface properties between the absorber and the resin is a beneficial approach. Summary of the invention

[0003] The purpose of the present invention is to provide a radar absorbing material having low-frequency radar wave absorption capability and high elasticity and high toughness and a preparation method thereof.

[0004] The technical solution of the present invention:

[0005] A high-elasticity and high-toughness low-frequency radar absorbing material, which uses a two-component polyurethane resin as a matrix, uses a sheet-shaped microwave absorber that has been modified by coating the surface of an amino alcohol mixture with a long-chain molecular structure as a filler, and is compounded by adding an organic dispersant, a defoamer, a softener, and a diluent; the two-component polyurethane resin comprises two components A and B, wherein the component A is a high-molecular-weight polyester resin with a long-chain molecular structure containing terminal hydroxyl groups, and the component B is a low-molecular-weight isocyanate grafted polyester resin; wherein the mixing mass ratio of the two components A to B is 100:2 to 100:20; the mass fraction of the two-component polyurethane resin in the absorbing material is 19% to 45%; the amino alcohol mixture is a mixture of 5-amino-1-pentanol and 6-amino-1-hexanol, wherein 5 The mixing mass ratio of amino-1-pentanol and 6-amino-1-hexanol is 100:50-100:200; the organic dispersant is BYK161, and its mass fraction in the absorbing material is 0.1%-10%; the defoamer is BYK055, and its mass fraction in the absorbing material is 0.1%-10%; the softener is a mixture of dibutyl phthalate and polyetheramine D2000, and the mixing mass ratio of the two is 100:20-100:500, and the mass fraction of the softener in the absorbing material is 0.1%-10%; the diluent is a mixture of cyclohexanone, butanone and butyl acetate, and the mixing mass ratio of the three is 1:(0.2-5):(0.1-10), and the mass fraction of the diluent in the absorbing material is 5%-25%.

[0006] The microwave absorbent filler is a sheet-like composite ferromagnetic material containing iron, cobalt and nickel, which is coated on the surface of an amino alcohol mixture with a long-chain molecular structure, and the mass fraction of the filler in the microwave absorbing material is 54% to 80%.

[0007] The flaky composite ferromagnetic material is a regular or irregular flaky powder with a length and width of about tens of microns and a thickness of about hundreds of nanometers.

[0008] The mixing mass ratio of the two components A and B of the two-component polyurethane resin is 100:10; the mass fraction of the two-component polyurethane resin in the absorbing material is 20%.

[0009] The mass fraction of the organic dispersant in the absorbing material is 1%, and the mass fraction of the defoaming agent in the absorbing material is 1%.

[0010] The mixing mass ratio of dibutyl phthalate and polyetheramine D2000 in the softener is 100:200; the mass fraction of the softener in the absorbing material is 1.5%.

[0011] The mixed mass ratio of cyclohexanone, butanone and butyl acetate in the diluent is 1:1.5:3, and the mass fraction of the diluent in the absorbing material is 10%.

[0012] The surface coating process comprises the following specific steps:

[0013] (1) mixing a flaky composite ferromagnetic material powder, an amino alcohol mixture, and anhydrous ethanol in a mass ratio of 1:(2-5):(1-2), adding zirconium oxide beads thereto, grinding the mixture in a planetary ball mill for 1-2 hours, and filtering out the zirconium oxide beads to obtain a mixed slurry 1;

[0014] (2) filtering the mixed slurry 1, and after filtering and drying, adding anhydrous ethanol again for cleaning and filtering, the mass ratio of anhydrous ethanol to the flaky powder in step (1) is (1-2):1; filtering the liquid and drying, obtaining a paste 1;

[0015] (3) drying the paste in a constant temperature environment at normal pressure at a temperature of 80° C. to 100° C. for 8 to 12 hours to obtain a dry solid block;

[0016] (4) The solid block is crushed and sieved to obtain a surface-coated and modified flaky microwave absorbent powder.

[0017] A method for preparing a high-elasticity and high-toughness low-frequency radar absorbing material, the method comprising the following steps:

[0018] (1) adding a diluent to component A of a two-component polyurethane resin, stirring the mixture at a temperature ranging from 20° C. to 35° C. for 0.5 hour to obtain a dispersion 1;

[0019] (2) adding an organic dispersant and a defoaming agent to the dispersion liquid 1, stirring for 0.5 hours at a temperature range of 20° C. to 35° C. to make the dispersion liquid 2 uniformly dispersed;

[0020] (3) adding the flaky microwave absorbent modified by the surface coating process to the dispersion liquid 2, stirring at a temperature range of 40° C. to 50° C. for 1 to 2 hours to obtain a dispersion liquid 3;

[0021] (4) Add component B of the two-component polyurethane resin to the dispersion liquid 3, and stir at a temperature range of 20° C. to 35° C. for 0.5 hour to prepare an absorbing material.

[0022] Beneficial effects of the present invention: The present invention designs and develops a new surface coating treatment process to treat the surface of low-frequency flaky composite ferromagnetic materials, improves the interface characteristics between the absorber and the resin, and finally obtains a low-frequency radar absorbing material with high elasticity and high toughness, supplemented by the optimization of the resin matrix and a variety of additives, and realizes the comprehensive requirements of high toughness, high elasticity, and excellent construction performance of the thick low-frequency radar wave absorbing material while meeting the requirements of electromagnetic wave absorption performance. The various properties of the developed low-frequency, high-elasticity, high-toughness low-frequency radar absorbing material have reached an advanced level that can be fully applied and long-term reliable. DETAILED DESCRIPTION

[0023] Principle of the invention: Low-frequency radar absorbing materials generally use ferromagnetic materials with flaky structural characteristics and higher magnetic permeability as absorbers. Compared with spherical absorbers, flaky absorber fillers have anisotropy and a larger specific surface area. The performance of the interface between the absorber and the resin has a significant impact on the overall physical and chemical properties of the absorbing material, resulting in a decrease in the toughness and elasticity of the absorbing coating. In addition, the flaky absorber filler is anisotropic and prone to irregular stacking to form pores, which will further destroy the overall toughness and elasticity of the absorbing coating. The flaky absorber filler is surface coated to improve the continuity of the interface between the absorber and the resin. At the same time, an organic polymer resin with good toughness and elasticity is selected as the matrix to prepare the absorbing coating. This can effectively improve the overall toughness and elasticity of the absorbing coating while ensuring the requirements of low-frequency electromagnetic wave absorption performance, while meeting the comprehensive requirements of excellent construction performance and other aspects.

[0024] The following is a detailed description of the embodiments of the present invention. It should be emphasized that the following description is only exemplary and is not intended to limit the scope and application of the present invention.

[0025] A high-elasticity and high-toughness low-frequency radar absorbing material, which uses a two-component polyurethane resin as a matrix, uses a sheet-shaped microwave absorber modified by coating the surface of an amino alcohol mixture with a long-chain molecular structure as a filler, and is compounded by adding an organic dispersant, a defoamer, a softener, and a diluent; the two-component polyurethane resin comprises two components A and B, wherein the component A is a high-molecular-weight polyester resin with a long-chain molecular structure containing terminal hydroxyl groups, and the component B is a low-molecular-weight isocyanate grafted polyester resin; wherein the mixing mass ratio of the two components A to B is 100:2-100:20; the mass fraction of the two-component polyurethane resin in the absorbing material is 19%-45%; the amino alcohol mixture is a mixture of 5-amino-1-pentanol and 6-amino-1-hexanol, wherein the mixing mass ratio of 5-amino-1-pentanol to 6-amino-1-hexanol is 100:50-100:200; the organic dispersant is BYK1 61, whose mass fraction in the absorbing material is 0.1% to 10%; the defoaming agent is BYK055, whose mass fraction in the absorbing material is 0.1% to 10%; the softener is a mixture of dibutyl phthalate and polyetheramine D2000, the mixing mass ratio of the two is 100:20 to 100:500, and the mass fraction of the softener in the absorbing material is 0.1% to 10%; the diluent is a mixture of cyclohexanone, butanone and butyl acetate, the mixing mass ratio of the three is 1:(0.2 to 5):(0.1 to 10), and the mass fraction of the diluent in the absorbing material is 5% to 25%.

[0026] The microwave absorbent filler is a sheet-like composite ferromagnetic material containing iron, cobalt and nickel, which is coated on the surface of an amino alcohol mixture with a long-chain molecular structure, and the mass fraction of the filler in the microwave absorbing material is 54% to 80%.

[0027] The flaky composite ferromagnetic material is a regular or irregular flaky powder with a length and width of about tens of microns and a thickness of about hundreds of nanometers.

[0028] The mixing mass ratio of the two components A and B of the two-component polyurethane resin is 100:10; the mass fraction of the two-component polyurethane resin in the absorbing material is 20%.

[0029] The mass fraction of the organic dispersant in the absorbing material is 1%, and the mass fraction of the defoaming agent in the absorbing material is 1%.

[0030] The mixing mass ratio of dibutyl phthalate and polyetheramine D2000 in the softener is 100:200; the mass fraction of the softener in the absorbing material is 1.5%.

[0031] The mixed mass ratio of cyclohexanone, butanone and butyl acetate in the diluent is 1:1.5:3, and the mass fraction of the diluent in the absorbing material is 10%.

[0032] The surface coating process comprises the following specific steps:

[0033] (1) mixing a flaky composite ferromagnetic material powder, an amino alcohol mixture, and anhydrous ethanol in a mass ratio of 1:(2-5):(1-2), adding zirconium oxide beads thereto, grinding the mixture in a planetary ball mill for 1-2 hours, and filtering out the zirconium oxide beads to obtain a mixed slurry 1;

[0034] (2) filtering the mixed slurry 1, and after filtering and drying, adding anhydrous ethanol again for cleaning and filtering, the mass ratio of anhydrous ethanol to the flaky powder in step (1) is (1-2):1; filtering the liquid and drying, obtaining a paste 1;

[0035] (3) drying the paste in a constant temperature environment at normal pressure at a temperature of 80° C. to 100° C. for 8 to 12 hours to obtain a dry solid block;

[0036] (4) The solid block is crushed and sieved to obtain a surface-coated and modified flaky microwave absorbent powder.

[0037] A method for preparing a high-elasticity and high-toughness low-frequency radar absorbing material, the method comprising the following steps:

[0038] (1) adding a diluent to component A of a two-component polyurethane resin, stirring the mixture at a temperature ranging from 20° C. to 35° C. for 0.5 hour to obtain a dispersion 1;

[0039] (2) adding an organic dispersant and a defoaming agent to the dispersion liquid 1, stirring for 0.5 hours at a temperature range of 20° C. to 35° C. to make the dispersion liquid 2 uniformly dispersed;

[0040] (3) adding the flaky microwave absorber modified by the surface coating process to the dispersion liquid 2, stirring at a temperature range of 40° C. to 50° C. for 1 to 2 hours to obtain a dispersion liquid 3;

[0041] (4) Add component B of the two-component polyurethane resin to the dispersion liquid 3, and stir at a temperature range of 20° C. to 35° C. for 0.5 hour to obtain an absorbing material.

[0042] Further features of the present invention will become apparent from the following description of exemplary embodiments.

[0043] Example 1

[0044] A high-elasticity and high-toughness low-frequency radar absorbing material, which uses a two-component polyurethane resin as a matrix, uses a sheet-like microwave absorber that has been modified by coating the surface of an amino alcohol mixture with a long-chain molecular structure as a filler, and is compounded by adding an organic dispersant, a defoamer, a softener, and a diluent. The two-component polyurethane resin is ECUST-PU, which includes two components A and B, wherein component A is a high molecular weight polyester resin with a long-chain molecular structure containing terminal hydroxyl groups, and component B is a low molecular weight isocyanate grafted polyester resin. The mixing mass ratio of the two components A and B is 100:7.5. The mass fraction of ECUST-PU two-component polyurethane in the absorbing material is 19%. The organic dispersant is BYK161, and its mass fraction in the coating is 0.4%. The defoamer is BYK055, and its mass fraction in the coating is 0.4%. The softener is a mixture of dibutyl phthalate and polyetheramine D2000, the mass ratio of which is 100:20; the mass fraction of the softener in the coating is 0.2%. The diluent is a mixture of cyclohexanone, butanone and butyl acetate, the mass ratio of which is 1:1.5:3.

[0045] The microwave absorbent filler is a flaky composite ferromagnetic material containing iron, cobalt and nickel elements, which is coated on the surface of an amino alcohol mixture with a long-chain molecular structure, and the mass fraction in the microwave absorbent material is 70%. The amino alcohol mixture is a mixture of 5-amino-1-pentanol and 6-amino-1-hexanol, wherein the mass ratio of 5-amino-1-pentanol to 6-amino-1-hexanol is 100:50. The specific coating process is: the composite magnetic material, the amino alcohol mixture and anhydrous ethanol are mixed in a mass ratio of 1:2:1 and then placed in a planetary ball mill for grinding for 2 hours to obtain a mixed slurry. The mixed slurry is then filtered; after the liquid is filtered and dried, anhydrous ethanol is added again for cleaning and filtration, the mass ratio of anhydrous ethanol to flaky powder is 1:1, and a paste is obtained; the paste is placed in a constant pressure and temperature environment for drying, and a dry solid block is obtained; the drying temperature is 80°C, the drying time is 12 hours, and a dry solid block is obtained; the solid block is crushed and sieved to obtain a flaky microwave absorbent powder after surface coating and modification.

[0046] A method for preparing a high-elasticity and high-toughness low-frequency radar absorbing material, the method comprising the following steps:

[0047] (1) adding a diluent to component A of a two-component polyurethane resin and stirring the mixture at 25° C. for 0.5 hours to obtain a dispersion 1;

[0048] (2) adding an organic dispersant and a defoaming agent to the dispersion liquid 1, stirring for 0.5 hours at 25° C. to make the dispersion liquid 2 uniformly dispersed;

[0049] (3) adding the flaky microwave absorber modified by the surface coating process to the dispersion liquid 2, stirring at 40° C. for 2 hours to obtain the dispersion liquid 3;

[0050] (4) Adding component B of the two-component polyurethane resin to the dispersion liquid 3, stirring at 25° C. for 0.5 hour, to obtain an absorbing material.

[0051] Example 2

[0052] A high-elasticity and high-toughness low-frequency radar absorbing material, which uses a two-component polyurethane resin as a matrix, uses a sheet-like microwave absorber that has been modified by coating the surface of an amino alcohol mixture with a long-chain molecular structure as a filler, and is compounded by adding an organic dispersant, a defoamer, a softener, and a diluent. The two-component polyurethane resin is ECUST-PU, which includes two components A and B, wherein component A is a high molecular weight polyester resin with a long-chain molecular structure containing terminal hydroxyl groups, and component B is a low molecular weight isocyanate grafted polyester resin. The mixing mass ratio of components A and B is 100:5. The mass fraction of ECUST-PU two-component polyurethane in the absorbing material is 28%. The organic dispersant is BYK1 61, and its mass fraction in the coating is 0.7%. The defoamer is BYK055, and its mass fraction in the coating is 0.7%. The softener is a mixture of dibutyl phthalate and polyetheramine D2000, the mass ratio of which is 100:50; the mass fraction of the softener in the coating is 0.6%. The diluent is a mixture of cyclohexanone, butanone and butyl acetate, the mass ratio of which is 1:1:2.

[0053] The microwave absorbent filler is a flaky composite ferromagnetic material containing iron, cobalt and nickel elements, which is coated on the surface of an amino alcohol mixture with a long-chain molecular structure, and the mass fraction of the amino alcohol mixture in the microwave absorbing material is 65%. The amino alcohol mixture is a mixture of 5-amino-1-pentanol and 6-amino-1-hexanol, wherein the mass ratio of 5-amino-1-pentanol to 6-amino-1-hexanol is 100:100. The specific coating process is: the composite magnetic material, the amino alcohol mixture and anhydrous ethanol are mixed in a mass ratio of 1:2:2 and then ground in a planetary ball mill for 1.5 hours to obtain a mixed slurry. The mixed slurry is then filtered; after the liquid is filtered and dried, anhydrous ethanol is added again for cleaning and filtering, the mass ratio of anhydrous ethanol to flaky powder is 2:1, and a paste is obtained; the paste is placed in a constant pressure and temperature environment for drying, and a dry solid block is obtained; the drying temperature is 90°C, the drying time is 10 hours, and a dry solid block is obtained; the solid block is crushed and sieved to obtain a flaky microwave absorbent powder after surface coating and modification.

[0054] A method for preparing a high-elasticity and high-toughness low-frequency radar absorbing material, the method comprising the following steps:

[0055] (1) adding a diluent to component A of a two-component polyurethane resin, stirring the mixture at 35° C. for 0.5 hours to obtain a dispersion 1;

[0056] (2) adding an organic dispersant and a defoaming agent to the dispersion liquid 1, stirring at 35° C. for 0.5 hour to make the dispersion uniform, thereby preparing a dispersion liquid 2;

[0057] (3) adding the flaky microwave absorber modified by the surface coating process to the dispersion liquid 2, stirring at 50° C. for 1 hour to obtain the dispersion liquid 3;

[0058] (4) Adding component B of the two-component polyurethane resin to the dispersion 3, stirring at 35° C. for 0.5 hour, to prepare an absorbing material.

[0059] Example 3

[0060] A high-elasticity and high-toughness low-frequency radar absorbing material, which uses a two-component polyurethane resin as a matrix, uses a sheet-shaped microwave absorber that has been modified by coating the surface of an amino alcohol mixture with a long-chain molecular structure as a filler, and is compounded by adding an organic dispersant, a defoamer, a softener, and a diluent. The two-component polyurethane resin is ECUST-PU, which includes two components A and B, wherein component A is a high molecular weight polyester resin with a long-chain molecular structure containing terminal hydroxyl groups, and component B is a low molecular weight isocyanate grafted polyester resin. The mixing mass ratio of components A and B is 100:15. The mass fraction of ECUST-PU two-component polyurethane in the absorbing material is 30%. The organic dispersant is BYK161, and its mass fraction in the coating is 0-3%. The defoamer is BYK055, and its mass fraction in the coating is 0.3%. The softener is a mixture of dibutyl phthalate and polyetheramine D2000, the mass ratio of which is 100:200; the mass fraction of the softener in the coating is 0.4%. The diluent is a mixture of cyclohexanone, butanone and butyl acetate, the mass ratio of which is 1:2:4.

[0061] The microwave absorbent filler is a flaky composite ferromagnetic material containing iron, cobalt and nickel elements, which is coated on the surface of an amino alcohol mixture with a long-chain molecular structure, and the mass fraction in the microwave absorbing material is 60%. The amino alcohol mixture is a mixture of 5-amino-1-pentanol and 6-amino-1-hexanol, wherein the mass ratio of 5-amino-1-pentanol to 6-amino-1-hexanol is 100:120. The specific coating process is: the composite magnetic material powder, the amino alcohol mixture and the anhydrous ethanol are mixed in a mass ratio of 1:5:1 and then placed in a planetary ball mill for grinding for 1.5 hours to obtain a mixed slurry. The mixed slurry is then filtered; after the liquid is filtered and dried, anhydrous ethanol is added again for cleaning and filtration, the mass ratio of anhydrous ethanol to flaky powder is 1.5:1, and a paste is obtained; the paste is placed in a constant pressure and temperature environment for drying, and a dry solid block is obtained; the drying temperature is 100°C, the drying time is 8 hours, and a dry solid block is obtained; the solid block is crushed and sieved to obtain a flaky microwave absorbent powder after surface coating and modification.

[0062] A method for preparing a high-elasticity and high-toughness low-frequency radar absorbing material, the method comprising the following steps:

[0063] (1) adding a diluent to component A of a two-component polyurethane resin and stirring the mixture at 25° C. for 0.5 hours to obtain a dispersion 1;

[0064] (2) adding an organic dispersant and a defoaming agent to the dispersion liquid 1, stirring at 30° C. for 0.5 hour to make the dispersion uniform, thereby preparing a dispersion liquid 2;

[0065] (3) adding the flaky microwave absorber modified by the surface coating process to the dispersion liquid 2, stirring at 45° C. for 1.5 hours to obtain the dispersion liquid 3;

[0066] (4) Adding component B of the two-component polyurethane resin to the dispersion liquid 3, stirring at 25° C. for 0.5 hour, to obtain an absorbing material.

[0067] Example 4

[0068] A high-elasticity and high-toughness low-frequency radar absorbing material, which uses a two-component polyurethane resin as a matrix, uses a sheet-like microwave absorber that has been modified by coating the surface of an amino alcohol mixture with a long-chain molecular structure as a filler, and adds an organic dispersant, a defoamer, a softener, and a diluent to compound. The two-component polyurethane resin is ECUST-PU, which includes two components A and B, wherein component A is a high molecular weight polyester resin with a long-chain molecular structure containing terminal hydroxyl groups, and component B is a low molecular weight isocyanate grafted polyester resin. The mixing mass ratio of components A and B is 100:20. The mass fraction of ECUST-PU two-component polyurethane in the absorbing material is 37%. The organic dispersant is BYK161, and its mass fraction in the coating is 0.2%. The defoamer is BYK055, and its mass fraction in the coating is 0.3%. The softener is a mixture of dibutyl phthalate and polyetheramine D2000, the mass ratio of which is 100:20; the mass fraction of the softener in the coating is 0.5%. The diluent is a mixture of cyclohexanone, butanone and butyl acetate, the mass ratio of which is 1:4:8.

[0069] The microwave absorbent filler is a flaky composite ferromagnetic material containing iron, cobalt and nickel elements, which is coated on the surface of an amino alcohol mixture with a long-chain molecular structure, and the mass fraction of the amino alcohol mixture in the microwave absorbing material is 56%. The amino alcohol mixture is a mixture of 5-amino-1-pentanol and 6-amino-1-hexanol, wherein the mass ratio of 5-amino-1-pentanol to 6-amino-1-hexanol is 100:200. The specific coating process is: the composite magnetic material, the amino alcohol mixture and anhydrous ethanol are mixed in a mass ratio of 1:3.5:1.5 and then placed in a planetary ball mill for grinding for 2 hours to obtain a mixed slurry. The mixed slurry is then filtered; after the liquid is filtered and dried, anhydrous ethanol is added again for cleaning and filtration, the mass ratio of anhydrous ethanol to flaky powder is 1:1, and a paste is obtained; the paste is placed in a constant pressure and temperature environment for drying, and a dry solid block is obtained; the drying temperature is 85°C, and the drying time is 12 hours to obtain a dry solid block; the solid block is crushed and sieved to obtain a surface-coated and modified flaky microwave absorbent powder.

[0070] A method for preparing a high-elasticity and high-toughness low-frequency radar absorbing material, the method comprising the following steps:

[0071] (1) adding a diluent to component A of a two-component polyurethane resin, stirring the mixture at 30° C. for 0.5 hours to obtain a dispersion 1;

[0072] (2) adding an organic dispersant and a defoaming agent to the dispersion liquid 1, stirring at 30° C. for 0.5 hour to make the dispersion uniform, thereby preparing a dispersion liquid 2;

[0073] (3) adding the flaky microwave absorber modified by the surface coating process to the dispersion liquid 2, stirring at 50° C. for 1 hour to obtain the dispersion liquid 3;

[0074] (4) Adding component B of the two-component polyurethane resin to the dispersion liquid 3, stirring at 25° C. for 0.5 hour, to obtain an absorbing material.

[0075] The above contents are further detailed descriptions of the present invention in combination with specific / preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, they can also make several substitutions or modifications to these described embodiments without departing from the concept of the present invention, and these substitutions or modifications should be regarded as belonging to the protection scope of the present invention.

Claims

1. A high elasticity and high toughness low frequency radar absorbing material, characterized in that: The microwave absorbing material uses a two-component polyurethane resin as a matrix, adopts a sheet-like composite ferromagnetic material that has been modified by coating the surface of an amino alcohol mixture with a long-chain molecular structure as a microwave absorbent filler, and is compounded by adding an organic dispersant, a defoamer, a softener, and a diluent; the two-component polyurethane resin comprises two components A and B, wherein the component A is a high-molecular-weight polyester resin with a long-chain molecular structure containing terminal hydroxyl groups, and the component B is a low-molecular-weight isocyanate grafted polyester resin; wherein the mixing mass ratio of the two components A to B is 100:2-100:20; the mass fraction of the two-component polyurethane resin in the microwave absorbing material is 19%-37%; the amino alcohol mixture The compound is a mixture of 5-amino-1-pentanol and 6-amino-1-hexanol, wherein the mixing mass ratio of 5-amino-1-pentanol to 6-amino-1-hexanol is 100:50-100:200; the organic dispersant is BYK161, and its mass fraction in the absorbing material is 0.1%-10%; the defoaming agent is BYK055, and its mass fraction in the absorbing material is 0.1%-10%; the softener is a mixture of dibutyl phthalate and polyetheramine D2000, and the mixing mass ratio of the two is 100:20-100:500, and the mass fraction of the softener in the absorbing material is 0.1%-10%; The diluent is a mixture of cyclohexanone, butanone and butyl acetate, the mass ratio of the three is 1: (0.2-5): (0.1-10), and the mass fraction of the diluent in the absorbing material is 5%-10%.

2. The high elasticity and high toughness low frequency radar absorbing material according to claim 1, characterized in that: The microwave absorbent filler is a sheet-like composite ferromagnetic material containing iron, cobalt and nickel, which is coated on the surface of an amino alcohol mixture with a long-chain molecular structure, and the mass fraction of the filler in the microwave absorbing material is 56% to 70%.

3. The high elasticity and high toughness low frequency radar absorbing material according to claim 1, characterized in that: The flaky composite ferromagnetic material is a regular or irregular flaky powder.

4. The high elasticity and high toughness low frequency radar absorbing material according to claim 1, characterized in that: The mixing mass ratio of the two components A and B of the two-component polyurethane resin is 100:10; the mass fraction of the two-component polyurethane resin in the absorbing material is 20%.

5. The high elasticity and high toughness low frequency radar absorbing material according to claim 1, characterized in that: The mass fraction of the organic dispersant in the absorbing material is 1%, and the mass fraction of the defoaming agent in the absorbing material is 1%.

6. The high elasticity and high toughness low frequency radar absorbing material according to claim 1, characterized in that: The mixing mass ratio of dibutyl phthalate and polyetheramine D2000 in the softener is 100:200; the mass fraction of the softener in the absorbing material is 1.5%.

7. The high elasticity and high toughness low frequency radar absorbing material according to claim 1, characterized in that: The mixed mass ratio of cyclohexanone, butanone and butyl acetate in the diluent is 1:1.5:3, and the mass fraction of the diluent in the absorbing material is 10%.

8. The high elasticity and high toughness low frequency radar absorbing material according to claim 1, characterized in that: The surface coating process comprises the following specific steps: (1) mixing a flaky composite ferromagnetic material powder, an amino alcohol mixture, and anhydrous ethanol in a mass ratio of 1:(2-5):(1-2), adding zirconium oxide beads thereto, grinding the mixture in a planetary ball mill for 1-2 hours, and filtering out the zirconium oxide beads to obtain a mixed slurry 1; (2) filtering the mixed slurry 1, and after filtering and drying, adding anhydrous ethanol again for cleaning and filtering, the mass ratio of anhydrous ethanol to the flaky powder in step (1) is (1-2):1; filtering the liquid and drying, obtaining a paste 1; (3) drying the paste in a constant temperature environment at normal pressure at a temperature of 80° C. to 100° C. for 8 to 12 hours to obtain a dry solid block; (4) The solid block is crushed and sieved to obtain a surface-coated and modified flaky microwave absorbent powder.

9. The method for preparing a high-elasticity, high-toughness, low-frequency radar absorbing material according to claim 1, characterized in that: The method takes the following steps: (1) adding a diluent to component A of a two-component polyurethane resin, stirring the mixture at a temperature ranging from 20° C. to 35° C. for 0.5 hour to obtain a dispersion 1; (2) adding an organic dispersant and a defoaming agent to the dispersion liquid 1, stirring for 0.5 hours at a temperature range of 20° C. to 35° C. to make the dispersion liquid 2 uniformly dispersed; (3) adding the flaky microwave absorber modified by the surface coating process to the dispersion liquid 2, stirring at a temperature range of 40° C. to 50° C. for 1 to 2 hours to obtain a dispersion liquid 3; (4) Add component B of the two-component polyurethane resin to the dispersion liquid 3, and stir at a temperature range of 20° C. to 35° C. for 0.5 hour to obtain an absorbing material.

Citation Information

Patent Citations

  • Anti-corrosion wave-absorbing coating and preparation method thereof

    CN107892871A

  • Method for spontaneous orientation of flake absorbent under condition of high fill ratio and wave-absorbing paint

    CN109957275A